THE DEVELOPMENT OF JAVELIN THROW LEARNING MODEL BASED GAMES IN ELEMENTARY SCHOOL - Musyabbih, Fauzan (Sriwijaya University Learning and Education International Conference, 2018)
This study aimed to produce a valid, practical, and effective Javelin Throwi learning product. This research method is Research and Development (R & D). Data collection was conducted with questionnaires obtained from evaluation of teacher of physical education and result of questioner by student. The results of the experiments for the small group experiments tested the average of the answers by percentage (83%), and large group trials showed the level of validity for the teacher of the physical education obtained average answers by percentage (78%), then the product has good category validity . Meanwhile, to see the practicality of small group testing on the students questionnaire filling obtained an average frequency distribution value of 79% while in large group trials obtained frequency distribution of 80.4% then the results show the level of practicality with good category. While for the effectiveness level on product aspect of motivation, result from small group test show relation aspect of motivation equal to 71,2% and large group trial is equal to 71,8% from cognitive, affective, and psikomotor aspect, hence result of tested product try shows the level of effectiveness with good category. Based on the above explanation has been found learning model of game-based javelin game given to the students have been effective so that it can be applied in learning Javelin Throw in Elementary School.